1994
DOI: 10.1037/0022-3514.66.2.350
|View full text |Cite
|
Sign up to set email alerts
|

Coping through emotional approach: Problems of conceptualizaton and confounding.

Abstract: Two studies supported hypotheses that (a) published scales tapping coping through processing and expressing emotion are confounded with psychopathology; (b) previously demonstrated relations between emotional approach coping (EAC) and maladjustment are partially spurious; and (c) EAC, when tapped by items uncontaminated by distress, is beneficial under specific conditions. In Study 1, 194 psychologists rated a majority of published items, but no author-constructed EAC item, as indicative of pathology. Study 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
317
3
7

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(339 citation statements)
references
References 39 publications
12
317
3
7
Order By: Relevance
“…However, when unconfounded emotional approach coping (acceptance and dealing with emotions) was measured in healthy individuals, a negative relation also emerged between emotion oriented coping and mental health (Stanton et al, 1994), although this relation was less strong than in our study. Thus, even though the emotion-oriented coping scale of the CISS could be criticized and seems to measure approaching emotions without accepting them (disengagement), it appears to be a sufficiently adequate method of determining the role of optimism in adapting to chronic disease.…”
Section: Discussioncontrasting
confidence: 91%
“…However, when unconfounded emotional approach coping (acceptance and dealing with emotions) was measured in healthy individuals, a negative relation also emerged between emotion oriented coping and mental health (Stanton et al, 1994), although this relation was less strong than in our study. Thus, even though the emotion-oriented coping scale of the CISS could be criticized and seems to measure approaching emotions without accepting them (disengagement), it appears to be a sufficiently adequate method of determining the role of optimism in adapting to chronic disease.…”
Section: Discussioncontrasting
confidence: 91%
“…However, many other higher order categories have been suggested that are not functionally homogeneous. For example, emotion-focused coping has been defined in ways that include both constructive emotional expression and explosive emotional discharge (Stanton, Danoff-Burg, Cameron, & Ellis, 1994). Because functionally different ways of coping can be triggered by different appraisals and have distinct (possibly opposite) consequences, categories that combine them are not useful for classifying ways of coping.…”
Section: Table 1 Desiderata For Category Systems To Classify Ways Of mentioning
confidence: 99%
“…When it is used as a higher order label in systems, there is literally no agreement about which lower order categories it encompasses. For example, in some systems, active attempts to calm oneself are considered emotion focused, whereas in others, uncontrolled venting and panic are included 3 (Stanton et al, 1994). Second, the "categories" of problem focused versus emotion focused are not mutually exclusive: Most ways of coping can serve both functions and thus could fit into both categories.…”
Section: Distinctions Among Functions Of Copingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Emotional Approach Coping Scale (EAC; Stanton, Danoff-Burg, Cameron, & Ellis, 1994) is an eight-item measure of coping that contains two 4-item subscales: emotional processing (e.g., "I take time to figure out what I'm really feeling") and emotional expression (e.g., "I take time to express my emotions"). Items are assessed on a four-point Likert-type scale (1 = "I usually don't do this at all"; 4 = "I usually do this a lot").…”
Section: The Structured Clinical Interview For Dsm-iv Axis I Disordermentioning
confidence: 99%